2018
DOI: 10.1007/s10439-018-2058-y
|View full text |Cite
|
Sign up to set email alerts
|

Material Processing and Design of Biodegradable Metal Matrix Composites for Biomedical Applications

Abstract: In recent years, biodegradable metallic materials have played an important role in biomedical applications. However, as typical for the metal materials, their structure, general properties, preparation technology and biocompatibility are hard to change. Furthermore, biodegradable metals are susceptible to excessive degradation and subsequent disruption of their mechanical integrity; this phenomenon limits the utility of these biomaterials. Therefore, the use of degradable metals, as the base material to prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Porous metallic materials have a wide-spaced rigid structure with low density and high mechanical strength, closely resembling the bone in vivo. Their shape and permeability are ideal for cell infiltration of the scaffold with good diffusion of nutrients, oxygen, and metabolic waste [ 120 , 122 ]. Their porosity is highly tunable, affecting the stiffness and strength of the scaffold, the diffusion capacity, and the extent of the migration of the cells, playing with the density of the tissue generated [ 123 , 124 ].…”
Section: Three-dimensional Cell Culture Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous metallic materials have a wide-spaced rigid structure with low density and high mechanical strength, closely resembling the bone in vivo. Their shape and permeability are ideal for cell infiltration of the scaffold with good diffusion of nutrients, oxygen, and metabolic waste [ 120 , 122 ]. Their porosity is highly tunable, affecting the stiffness and strength of the scaffold, the diffusion capacity, and the extent of the migration of the cells, playing with the density of the tissue generated [ 123 , 124 ].…”
Section: Three-dimensional Cell Culture Methodsmentioning
confidence: 99%
“…Their porosity is highly tunable, affecting the stiffness and strength of the scaffold, the diffusion capacity, and the extent of the migration of the cells, playing with the density of the tissue generated [ 123 , 124 ]. Biodegradable porous metallic scaffolds can be made by selective laser melting [ 125 ], powder metallurgy [ 126 ], injection of inert gas into a melt [ 127 ], sintering of particles [ 128 ], vacuum foaming [ 129 ], investment casting [ 130 ], thixocasting [ 131 ], and other methods [ 122 ].…”
Section: Three-dimensional Cell Culture Methodsmentioning
confidence: 99%
“…Microwave sintering is an advanced sintering method in which microwave irradiation is used to sinter the green compact in a short time period. It was reported that microwave sintering provides more uniform heating, low power consumption, and fast heating without any thermal gradient. Wan et al successfully prepared Mg/BG composites using this microwave sintering. The short densification time limits the reaction between Mg and BG particles in comparison to conventional sintering.…”
Section: Processing Of Mg Ceramic Reinforced Compositesmentioning
confidence: 99%
“…25 Over the past few years, biomedical scientists and engineers have developed biodegradable metallic materials to improve the regenerative capability of biomaterials and stimulate the desirable immune system responses leading to the biomaterial's success. 23,[26][27][28] Such materials are developed to adjust their function in the body based on the biochemical and biomechanical properties of bone tissue. 29 A biodegradable biomaterial acts as a support for the surrounding cells/tissue to grow in, and therefore guides the healing processes toward new bone formation.…”
Section: Introductionmentioning
confidence: 99%